(untitled) (International Journal of Engineering and Computer Science, 2017)
In Wireless Sensor Networks (WSNs), sensor nodes have limited battery power, so energy consumption is essential issue. Every sensor node can obtain its location information from GPS or other positioning system and send data to sink at any time. Wireless sensor networks (WSNs) are resource constrained. Energy is one of the most important resources in such networks. Therefore, optimal use of energy is necessary. Energyefficient routing protocol is proposed for WSNs. The protocol is reliable in terms of data delivery at the base station (BS). Mobility in sensor nodes and in the BS is considered. The proposed protocol is hierarchical and cluster based. Each cluster consists of one cluster head (CH) node, two deputy CH nodes, and some ordinary sensor nodes. Considering the reliability aspect of the protocol, it puts best effort to ensure a specified throughput level at the BS. Depending on the topology of the network, the data transmission from the CH node to the BS is carried out either directly or in multihop fashion. Index Terms-Energy efficiency, mobile base station (BS), mobile nodes, reliability, routing protocol, wireless sensor networks.